Evaluation of glycaemic index, starch-hydrolyzing enzymes inhibitory and antioxidant properties of tradition products of select biofortified cassava varieties - Kareem, B. (Kwara State University, 2022)
Provitamin A biofortified yellow-fleshed cassava is an important dietary source of β-Carotene. Before consumption, it is processed into traditional products (fufu, lafun and gari) that may influence its bioactivities. In this study, the effect of traditional processing on the antioxidant, starch-digesting enzymes inhibitory properties, and glycaemic index (GI) of biofortified yellow flesh cassava genotypes was evaluated. The carotenoids content of twenty-nine biofortified yellow cassava genotypes, grown at the International Institute of Tropical Agriculture (IITA) research field, Ibadan, was quantified using a reverse-phase HPLC system. Among these samples, the fifteen with the highest β-carotene content and three genotypes with the lowest β-carotene content were selected for physicochemical (pasting properties, proximate and carbohydrate profile), bioactive constituents (total phenolics, flavonoids, and tannins) and in vitro bioactivities (antioxidant and starch-digesting enzymes inhibitory) analyses. Significant differences (p < 0.05) existed in the bioactive constituents, carbohydrate, pasting properties, antioxidant and starch-digesting enzymes inhibitory of the selected cassava genotypes flour. Among these selected eighteen (18) cassava genotypes, 4 genotypes with high total carotenoids and phenolics contents (IITA-TMS-IBA182962, 183044, 182961 and 182986) and one genotype (IITA-TMS-IBA070337) with low total carotenoids and phenolics contents were further selected and processed into fufu, lafun and gari according to traditional processing methods. They were further analysed for bioactive contents, antioxidant and in vitro starch-hydrolyzing inhibitory activities. The bioactive constituents, antioxidant and starch-digesting enzymes inhibitory activities of the products were determined by spectrophotometric methods. The GI of the products was assessed in human subjects. The concentrations of the bioactive constituents of the products from different genotypes varied significantly (p < 0.05). among all the products, fufu had the highest bioactive constituents while gari had highest apparent retention properties of flavonoids and tannins among all the three products The ABTS*+ and DPPH* scavenging capacities and the reducing power of the products also differed significantly (p < 0.05), lafun from IITA-TMS-IBA182962 had the strongest ABTS*+ scavenging capacities, while IITA-TMS-IBA070337 had the strongest DPPH* scavenging capacities and reducing power. The α-amylase and α-glucosidase inhibitory activities of the three products differed significantly (p < 0.05), with the lafun from IITA-TMS-IBA070337 and IITA-TMS-IBA07033 having the strongest α-amylase and α-glucosidase inhibitory activity, respectively. Also, the lafun from IITA-TMS-182986 had the least GI, while the fufu from IITA-TMS-IBA070337 had the highest GI. Overall, the lafun from different genotypes of the cassava genotypes had the most potent antioxidant and starch-digesting enzymes inhibitory activities, and the least GI. Hence, lafun may be a promising dietary intervention targeting oxidative stress, hyperglycaemia, and their resultant type 2 diabetes.